Sao Tome and Principe : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Sao Tome and Principe is a small, island country with some 138,000 inhabitants; its resources are limited, and its GDP per capita is estimated at about USD 295 (1998). The economy is heavily dependent on cocoa, which accounts for 96 percent of export goods. The country has liberalized the economy and reduced the role of government in productive activities in the 1990s. The government has successfully implemented a staff-monitored program in 1998-99 that has turned around the primary budget balance from a deficit to a surplus, reduced inflation, and has helped improve real GDP growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet